SENI MUSIK HADRAH SEBAGI MEDIA KONSELING ISLAM DALAM MENGUBAH PERILAKU REMAJA - Farhatul Lailiyah; Mohamat Hadori; Samsul Arifin (Fakultas Dakwah Universitas Ibrahimy, 2024)
The problem of juvenile delinquency in Indonesia is the main problem faced today. Delinquency that occurs in teenagers is influenced by the social, emotional environment and the mindset of teenagers. The aim of this research is to describe the positive side of hadrah music as a medium for Islamic counseling for teenagers. This research uses a qualitative research method with a case study type of research. The results of the research that has been carried out can be concluded that teenagers can change deviant behavior to positive behavior, change interaction patterns, thought patterns, control emotions. Through the hadrah and sy’ir arts activities that they present, they are able to become wiser and wiser in their behavior.